Labor Market Segmentation in a Two-Sector Model of An Open Economy - Demekas, Dimitri (IMF Working Papers; Working Paper ;, 1990)
The paper examines formally the effects of labor market segmentation in a two-sector open economy model. The model demonstrates how the structure of the labor market affects the real exchange rate, defined as the relative price of traded and home goods, and is then used to examine the effects of two common labor market policies: increasing the degree of primary market coverage, and implementing wage restraint in the primary market. It is shown that increasing the degree of primary market coverage increases unemployment and leads to a real appreciation. Real wage restraint in the primary market, on the other hand, reduces unemployment, and has ambiguous but probably small effects on the real exchange rate.